OP0004 Collection and Management of Selected Comorbidities and Their Risk Factors in Chronic Inflammatory Rheumatic Diseases in Daily Practice in France. (15th July 2016) - Gossec, L.; Baillet, A.; Dadoun, S.; Daïen, C.; Berenbaum, F.; Dernis, E.; Fayet, F.; Hudry, C.; Mézières, M.; Pouplin, S.; Richez, C.; Saraux, A.; et al.
Abstract : Background: In chronic inflammatory rheumatic diseases including rheumatoid arthritis, spondyloarthritis and connective tissue diseases, comorbidities such as cardiovascular diseases and infections are sub-optimally prevented, screened and managed. EULAR recently developed points to consider to collect and report comorbidities but did not include the management phase. (ref) Objectives: To develop a pragmatic form to collect, report and give management recommendations for selected comorbidities and risk factors, from a rheumatologist perspective. Methods: Comorbidities were selected by an expert group of 18 persons, using the previous experience of the recent EULAR points to consider for comorbidities. (ref) The collection and reporting of these comorbidities and risk factors were adapted from the EULAR recommendations. (ref) To develop management recommendations, the process comprised (1) systematic literature reviews by 3 fellows and (2) a 2-day consensus process involving 110 experts (rheumatologists and health professionals). Votes of agreement (Likert 1–5 where 5 indicates full agreement) were obtained from the group. Results: The six selected comorbidities were ischemic cardiovascular diseases, malignancies, infections, gastrointestinal diseases, osteoporosis and depression. The literature review retrieved 158 articles, mostly developed for the general population. The consensus process led to a pragmatic reporting form to collect the existence of a comorbidity (eg heart failure yes/no), current treatment (e.g. stent yes/no), risk factors (e.g. hypertension), screening (e.g. mammography) and prevention (e.g. vaccination). Furthermore, existing management recommendations were adapted to rheumatologists (or developed when unavailable) leading to 28 practical forms. These include physical examination elements such as blood pressure or lymph node examination, prescribing screening procedures, and interpreting results to refer in a timely manner to appropriate other health professionals. Agreement was high (mean, 4.37 ± 0.33 on a 1–5 scale). Conclusions: Using an evidence-based approach followed by expert consensus, this initiative furthers the dissemination and the adaptation to a national context of the EULAR comorbidities initiative, and clearly defines what part of the management of comorbidities is potentially within the remit of rheumatologists. The pragmatic developed document should facilitate the periodical systematic review of patients suffering from chronic inflammatory rheumatic diseases. Next steps include dissemination and implementation of this document. References: Baillet A, Gossec L, et al. EULAR points to consider for reporting, screening and preventing selected comorbidities in chronic inflammatory rheumatic diseases in daily practice: A EULAR initiative. Annals of the Rheumatic diseases (submitted). Acknowledgement: Derived from the Rencontres d'Experts en Rhumatologie program, which was sponsored by AbbVie France. AbbVie employees were present during the Rencontres d'Experts en Rhumatologie meetings, but did not influence the scientific discussions. AbbVie did not review the content or have influence on this abstract. Disclosure of Interest: None declared